2003
DOI: 10.31887/dcns.2003.5.2/huwittchen
|View full text |Cite
|
Sign up to set email alerts
|

Mental disorders in primary care

Abstract: Current estimates indicate that 50% of the population experience at least one mental disorder in their lifetime and that at least 25% have suffered a mental disorder in the past year. recognition, diagnosis, treatment, and referral depend overwhelmingly on general practitioners, at least one third of whose consultations have a direct and explicit psychological component. Yet despite this intensive familiarization with the presentation of mental pathology, and the appropriateness of the primary care setting to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(55 citation statements)
references
References 42 publications
(16 reference statements)
1
50
1
3
Order By: Relevance
“…There is evidence that mental health services are more acceptable when they are decentralized and integrated into primary healthcare [ 19 , 20 ]. Moreover, research findings from previous studies indicated that Greeks display less favorable attitudes towards mental illness compared to people from other countries [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…There is evidence that mental health services are more acceptable when they are decentralized and integrated into primary healthcare [ 19 , 20 ]. Moreover, research findings from previous studies indicated that Greeks display less favorable attitudes towards mental illness compared to people from other countries [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…Both the high prevalence of mental disorders in the community and the reform of mental health services (e.g. reduction of psychiatric hospital beds) have resulted in a larger burden of people facing mental health problems in primary care settings [ 19 ]. Despite this however, the detection and management of mental disorders in primary care is still understudied.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, some authors have underlined that improving recognition of all mental health disorders in primary care might not be possible and that in fact identification rates of mental health disorders are not very different from those of physical disorders ( Wittchen, Mühlig, & Beesdo, 2003 ). They also argue that failed recognition might not only be due to GP's poor knowledge, but to a natural threshold in illness severity, whereby GPs will identify disorders that are above that threshold.…”
Section: Gps Are Not Poor At Identifying the Eds: Nadiamentioning
confidence: 99%